2008
DOI: 10.1007/s11695-008-9677-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications After Sleeve Gastrectomy for Morbid Obesity

Abstract: LSG is a safe procedure with low morbidity. Because leaks and reoperation in this series were preceded by large increments in intraabdominal pressure, attention to staple line reinforcements that increase burst pressure may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(118 citation statements)
references
References 22 publications
9
104
2
3
Order By: Relevance
“…The vertical sleeve gastroplasty is a new option for the treatment of obesity and is currently the fastest growing 13 worldwide, as a technique that keeps the gastrointestinal continuity, with less surgical time, good weight loss curve, lack of dumping syndrome (found often in gastric bypass), access to the biliary tree, no excluded stomach segment in the cavity (hindering future diagnosis of tumors), absence of malabsorption (with low levels of nutritional complications), and allowing continued operation Table 1 Table 1 Table 1 Table 1 Table 1 20 there was an average weight loss of 54-58% of the overweight five years after vertical gastroplasty . Dapri et al 21 reported a reduction in mean BMI to 34.4 kg/m2, similar to the results found in our study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical sleeve gastroplasty is a new option for the treatment of obesity and is currently the fastest growing 13 worldwide, as a technique that keeps the gastrointestinal continuity, with less surgical time, good weight loss curve, lack of dumping syndrome (found often in gastric bypass), access to the biliary tree, no excluded stomach segment in the cavity (hindering future diagnosis of tumors), absence of malabsorption (with low levels of nutritional complications), and allowing continued operation Table 1 Table 1 Table 1 Table 1 Table 1 20 there was an average weight loss of 54-58% of the overweight five years after vertical gastroplasty . Dapri et al 21 reported a reduction in mean BMI to 34.4 kg/m2, similar to the results found in our study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Mortality after sleeve gastroplasty is small, usually less than 0.5% 13,20,29 . In our study there was a case of death due to postoperative thromboembolism, despite the use of preventive measures and anticoagulant employee.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…3 Furthermore, its mortality rate (0.5%) is quite low. 4 SG popularity worldwide has grown significantly among bariatric/metabolic procedures and now encompasses 27.8% of procedures performed in the past 8 years. 5 Due to this rapid growth, new complications are sure to be noticed.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms proper correction and also gives idea of the places for the fixation stitches during gastropexy. [5][6][7] • Gastropexy: Attempt gastropexy by taking intermittent stitches involving posterior fixed structures like left crush, pancreatic capsule, and mesocolon.…”
Section: Discussionmentioning
confidence: 99%